2000
DOI: 10.1034/j.1600-051x.2000.027008537.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma lipid and blood glucose levels in patients with destructive periodontal disease

Abstract: Hyperlipidaemia and hyperglycaemia are major risk factors for cardiovascular disease. In recent years, some evidence has been presented that periodontal disease is associated with an increased risk of cardiovascular disease. To further elucidate this association, we have studied standard blood chemistry variables known as risk markers for cardiovascular disease in periodontally diseased and healthy subjects. We have measured levels of plasma lipids and fasting blood glucose in 39 subjects with moderate periodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

26
204
5
13

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 226 publications
(248 citation statements)
references
References 31 publications
26
204
5
13
Order By: Relevance
“…TC and LDL as well as TG. 6,21,27 The outcomes of our study support this overall conclusion. But most of the above mentioned studies were unable to infer a positive correlation with all the parameters of lipid profile (i.e.…”
Section: Jaypeesupporting
confidence: 86%
See 2 more Smart Citations
“…TC and LDL as well as TG. 6,21,27 The outcomes of our study support this overall conclusion. But most of the above mentioned studies were unable to infer a positive correlation with all the parameters of lipid profile (i.e.…”
Section: Jaypeesupporting
confidence: 86%
“…6,13,[21][22][23] Each of these studies has their own specifications such as definition of periodontal disease, assay for serum lipid levels, study design and number of cases. Others have shown lack of this relation.…”
Section: Jaypeementioning
confidence: 99%
See 1 more Smart Citation
“…High levels of LDL and triglycerides (TGR) were found to be associated with high alveolar bone loss using X-rays in the periodontitis group (6). Similarly, other authors found significant relations between the levels of TC, LDL, and TGR, and clinical periodontal disease (3,5). Despite this evidence, there is no consensus in the literature regarding this topic, as other studies reported no significant relation between periodontal status and lipid level alterations (7).…”
Section: Introductionmentioning
confidence: 96%
“…Recently, studies examining the relationship between periodontal disease and hyperlipidemia have shown that a greater systemic involvement may occur in patients exhibiting periodontal involvement (1)(2)(3)(4). Chronic exposure to bacterial lipopolysaccharides (LPS) can promote recruitment of defense cells which secrete alpha tumor necrosis factor (TNF-α) and interleukin-1 beta (IL-1β), thus increasing lipogenesis and lipolysis.…”
Section: Introductionmentioning
confidence: 99%